2019
DOI: 10.1073/pnas.1913485116
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory coreceptor IR8a governs larval feces-mediated competition avoidance in a hawkmoth

Abstract: Finding a suitable oviposition site is a challenging task for a gravid female moth. At the same time, it is of paramount importance considering the limited capability of most caterpillars to relocate to alternative host plants. The hawkmoth, Manduca sexta (Sphingidae), oviposits on solanaceous plants. Larvae hatching on a plant that is already attacked by conspecific caterpillars can face food competition, as well as an increased exposure to predators and induced plant defenses. Here, we show that feces from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 50 publications
2
67
0
1
Order By: Relevance
“…Females can help to reduce the level of competition faced by their offspring by avoiding laying eggs on or in hosts bearing a brood [31]. Previous studies have indicated that avoidance of occupied hosts is typically mediated by cues and/or signals associated with the ovipositing females, offspring, or insect feces [31][32][33][34][35]. Although studies have indicated that chemical changes in host plants can be used as host-marking pheromones by gravid females [36,37], such changes in plant compounds are associated with damage caused by oviposition or by tissue destruction by larvae or adults.…”
Section: Discussionmentioning
confidence: 99%
“…Females can help to reduce the level of competition faced by their offspring by avoiding laying eggs on or in hosts bearing a brood [31]. Previous studies have indicated that avoidance of occupied hosts is typically mediated by cues and/or signals associated with the ovipositing females, offspring, or insect feces [31][32][33][34][35]. Although studies have indicated that chemical changes in host plants can be used as host-marking pheromones by gravid females [36,37], such changes in plant compounds are associated with damage caused by oviposition or by tissue destruction by larvae or adults.…”
Section: Discussionmentioning
confidence: 99%
“…IRs were originally discovered by expression of olfactory neurons and belong to the ionotropic glutamate receptor (iGluR) gene family, a highly conserved family of ligand-gated ion channels ( Benton et al, 2009 ; Croset et al, 2010 ; Rytz et al, 2013 ). Recent functional studies indicate that IRs have diverse functions in chemical reception and participate in the sensation of odorants, temperature, humidity, and salt ( Chen et al, 2015 ; Zhang et al, 2019 ). GRs play key roles in the sensing of CO 2 , sugars, bitter compounds, salts, and some gustatory pheromones ( Dahanukar et al, 2007 ; Kwon et al, 2007 ; Wanner and Robertson, 2008 ; Kent and Robertson, 2009 ; Xu et al, 2012 ; Mang et al, 2016 ; Fleischer et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, IRs function reported in lepidopteran species is quite limited. However, recent research showed that IR8a was essential for acid-mediated feces avoidance in ovipositioning hawkmoth, Manduca sexta ( Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%